2020
DOI: 10.26804/capi.2020.01.01
|View full text |Cite
|
Sign up to set email alerts
|

A model of spontaneous flow driven by capillary pressure in nanoporous media

Abstract: The spontaneous capillary imbibition phenomenon is a fundamental mechanism in porous media with applications in many fields. In low permeability shale reservoirs, this flow driven by capillary pressure is extremely important due to the predominance of nanoscale pores, which enhance capillary pressure and weaken hydrodynamic viscous force. This paper presents the results of an analytical model for capillary rise in nano-channels by taking into consideration the effect of inherent surface roughness. Model predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 29 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Schebarchov and Hendy modified the LW equation considering a Navier slip length b at the nanoscale as follows Apart from considering slippage, inherent wall roughness and effective viscosity are also taken into account separately to accurately characterize the capillary imbibition behavior in nanopores based on the LW equation. The capillary imbibition model considering effective viscosity and slippage in nanopores can therefore be expressed as follows where c is the constant for water.…”
Section: Modifications and Extensions Of The Lw Equationmentioning
confidence: 99%
“…Schebarchov and Hendy modified the LW equation considering a Navier slip length b at the nanoscale as follows Apart from considering slippage, inherent wall roughness and effective viscosity are also taken into account separately to accurately characterize the capillary imbibition behavior in nanopores based on the LW equation. The capillary imbibition model considering effective viscosity and slippage in nanopores can therefore be expressed as follows where c is the constant for water.…”
Section: Modifications and Extensions Of The Lw Equationmentioning
confidence: 99%
“…In essence, capillary pressure is the pressure difference between vapor-phase pressure and liquid-phase pressure, which is inversely proportional to pore size. As a result, capillary pressure cannot be neglected at the nanoscale, which turns out to be relatively good at dramatically varying vapor-phase density and liquid-phase density [47,48], further affecting phase behavior. Notably, when compared with the conventional formula for capillary pressure, Formula (11) (designed for nanoconfined capillary pressure) takes into account the adsorption-phase thickness.…”
Section: Capillary Pressurementioning
confidence: 99%
“…Han et al experimentally investigated the infiltration of glycerin in a lyophobic nanoporous silica gel and found that the effective liquid viscosity is highly dependent on the pore size and the loading rate. Shen et al conducted experiments on the pressure-driven infiltration of deionized water into nanopores. The results demonstrate that spontaneous absorption in nanoporous media can be scaled and predicted.…”
Section: Introductionmentioning
confidence: 99%